Transcendentalising reduction: The Heuristic Role of the Phenomenological Epoché in the Metaphysics of Existential Thomism - Duchliński, Piotr; Mazur, Piotr S. (Forum philosophicum (Kraków, Poland), 2022)
The aim of the article is to outline the concept of transcendentalising reduction and to demonstrate what role it plays in Thomistic metaphysics. An adaptive interpretation has been used in the analyses by applying phenomenological thinking based on epoche reduction to Thomistic metaphysics. It was used to present the structure of transcendentalising reduction, which consists of several different epoché. Consistently applied, this reduction should lead to a neutralised concept of being as a subject of metaphysics expressed in the formula “being as being”. In conclusion, we note that the proposed interpretation opens the door to further research in which phenomenology could be used in metaphysical studies to a greater extent than has been the case to date.